HST-NICMOS Observations of M31's Metal Rich Globular Clusters and Their Surrounding Fields: II. Results - Stephens, A; Frogel, J; Freedman, W; Gallart, C; Jablonka, P; Ortolani, S; Renzini, A; Rich, R; Davies, R (2000)
We have obtained HST-NICMOS observations of five of M31's most metal rich globular clusters: G1, G170, G174, G177 and G280. For the two clusters farthest from the nucleus we statistically subtract the field population and estimate metallicities using K-(J-K) color-magnitude diagrams (CMDs). Based on the slopes of their infrared giant branches we estimate [Fe/H]=-1.22+/-0.43 for G1 and -0.15+/-0.37 for G280. We combine our infrared observations of G1 with two epochs of optical HST-WFPC2 V-band data and identify at least one LPV based on color and variability. The location of G1's giant branch in the K-(V-K) CMD is very similar to that of M107, indicating a higher metallicity than our purely infrared CMD: [Fe/H]=-0.9+/-0.2. For the field surrounding G280, we estimate the metallicity to be -1.3 with a spread of 0.5 from the slope and width of the giant branch. Based on the numbers and luminosities of the brightest giants, we conclude that only a small fraction of the stars in this field could be as young as 2 Gyr, while the majority have ages closer to 10 Gyr. The K-band luminosity functions (LFs) of the upper few magnitudes of G1 and G280, as well as for the fields surrounding all clusters, are indistinguishable from the LF measured in the bulge of our Galaxy. This indicates that these clusters are very similar to Galactic clusters, and at least in the surrounding fields observed, there are no significant populations of young luminous stars.